Language Shift of Holimombo Among Youth in Talaga Hamlet Luhu Village - Hadi, Putri Titian; Solissa, Everhard Markiano (Universitas Pattimura, 2025)
This study aims to describe the shift and factors of the shift among teenagers of Talaga Hamlet, Luhu Village, Huamual Sub-district, West Seram Regency. The research approach uses post-positivism with qualitative research type, descriptive method. The techniques used in data collection are observation, interview, documentation, recording and tapping techniques. While the instruments used are observation sheets, interview guidelines, recording devices and field notes. Based on the results of research in Talaga hamlet, the use of Holimombo language among adolescents in the family and social spheres of society is very rarely used. Holimombo language is only spoken by adults or the elderly when they communicate. Meanwhile, teenagers often communicate using Ambon Malay when interacting with friends, the community and parents. This happens because parents and the community rarely speak Holimombo when interacting with children/young people in Talaga hamlet. This phenomenon is caused by the intensity of the use of Ambon Malay language in daily conversations to the point of displacing local languages.